2022
DOI: 10.1246/bcsj.20220062
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Spin Interactions of 1D Chains of Different-Sized Nitroxide Radicals Incorporated in the Organic 1D Nanochannels of Tris(o-phenylenedioxy)cyclotriphosphazene

Abstract: Variable-temperature electron spin resonance (ESR) was measured for one-dimensional (1D) molecular chains formed using different-sized organic radicals incorporated into the 1D nanochannels of tris(o-phenylenedioxy)cyclotriphosphazene (TPP). The ESR spectra for the molecular chains of 4-oxo-2,2,6,6-tetramethyl-1-piperidinyl-1-oxyl (TEMPONE) incorporated in the TPP nanochannels ([TPP-TEMPONE]) exhibited anisotropic three-dimensional (3D) spin diffusion at temperatures close to room temperature. In contrast, 1D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Kobayashi et al constructed one-dimensional nanochannels using tris(o-phenylenedioxy)cyclotriphosphazene and observed that organic radicals of different sizes that were trapped in 4-oxo-2,2,6,6-tetramethyl-1-piperidinyl-1-oxyl molecular chain were investigated by temperature-variable electron spin resonance. [61] Spin interactions of organic radical onedimensional molecular chains formed in nanochannels are affected by the size, dynamics, and temperature of the guest molecules. It is found that one-dimensional spin diffusion is enhanced at low temperatures in size-tunable nanochannels.…”
Section: Nanoarchitectonics In Structural Organization For Physics Re...mentioning
confidence: 99%
“…Kobayashi et al constructed one-dimensional nanochannels using tris(o-phenylenedioxy)cyclotriphosphazene and observed that organic radicals of different sizes that were trapped in 4-oxo-2,2,6,6-tetramethyl-1-piperidinyl-1-oxyl molecular chain were investigated by temperature-variable electron spin resonance. [61] Spin interactions of organic radical onedimensional molecular chains formed in nanochannels are affected by the size, dynamics, and temperature of the guest molecules. It is found that one-dimensional spin diffusion is enhanced at low temperatures in size-tunable nanochannels.…”
Section: Nanoarchitectonics In Structural Organization For Physics Re...mentioning
confidence: 99%
“…Furthermore, we can analyze and understand phenomena in those nanoregions [ 168 , 169 , 170 , 171 ]. Such technologies have been applied to analytical chemistry [ 172 , 173 , 174 , 175 , 176 ] and physical chemistry [ 177 , 178 , 179 , 180 , 181 ], and the impact of the structure of a material on its function has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we can analyze and understand phenomena in those nanoregions [168][169][170][171]. Such technologies have been applied to analytical chemistry [172][173][174][175][176] and physical chemistry [177][178][179][180][181], and the impact of the structure of a material on its function has been studied. The next step in nanotechnology is to establish a methodology to assemble new functional materials based on the knowledge of nanotechnology.…”
Section: Introductionmentioning
confidence: 99%